Autologous precision-cut lung slice co-culture models for studying macrophage-driven fibrosis - Chang, So-Yi; Chang, Wen-Hsin; Yang, David C.; Hong, Qi-Sheng; Hsu, Ssu-Wei; Wu, Reen; Chen, Ching-Hsien (Frontiers in Physiology, 2025)
Precision-cut lung slices (PCLS) are commonly used as an ex vivo model to study lung fibrosis; however, traditional models lack immune cell infiltration, including the recruitment of monocytes and macrophages, which are critical for inflammation and fibrosis. To address this limitation, we developed novel autologous PCLS-immune co-culture models that better replicate the processes of inflammation, repair, and immune cell recruitment associated with fibrosis. Fibrotic responses to nicotine, cigarette smoke extract (CSE), and a fibrosis-inducing cocktail (FC) were first evaluated in PCLS containing only tissue-resident macrophages, with upregulation of α-SMA-expressing fibroblasts confirmed by immunofluorescence and Western blotting, and collagen deposition quantified using Sirius Red staining. To study macrophage recruitment, we employed an indirect co-culture model using transwells to approximate blood vessel function. Chemotactic studies revealed increased migration of autologous bone marrow-derived macrophages (BMDMs) toward and infiltration into CSE-injured PCLS. In a direct co-culture model simulating the repair phase of fibrosis, PCLS exposed to CSE and FC showed further increased collagen deposition in the presence of autologous BMDMs, but not heterologous ones. These findings suggest that our novel PCLS-immune co-culture models provide a platform for studying macrophage involvement in fibrosis and offer potential for developing macrophage-targeted therapeutic strategies in pulmonary fibrosis.